Self-Criticism in Emerging Adulthood With Adverse Childhood Experiences Increases Depression, Anxiety, and Stress: [Kritik Diri Pada Dewasa Awal Dengan Pengalaman Buruk di Masa Kecil Meningkatkan Depresi, Kecemasan, dan Stres] - Leman, Helena Kristina; Arjadi, Retha (ANIMA Indonesian Psychological Journal, 2023)
The rate of child maltreatment in Indonesia is relatively high. Adverse childhood experiences are associated with poor mental health outcomes on individuals in emerging adulthood. However, the association between adverse childhood experiences and mental health problems has not been explored rigorously in the context of Indonesia. Therefore, this study examines the effect of self-criticism on depression, anxiety, and stress on individuals in emerging adulthood with adverse childhood experiences. Individuals in emerging adulthood, aged 18-25 years, lived in Indonesia, and had a history of adverse childhood experiences, were included as the study sample (N = 450). Participants filled out a self-criticism questionnaire utilizing the Levels of Self-Criticism (LOSC) instrument which measured comparative self-criticism and internalized self-criticism. Depression, anxiety, and stress were measured using Depression, Anxiety, and Stress Scale 42 (DASS-42). The results confirmed that comparative self-criticism and internalized self-criticism significantly contributed to the increase of depression, anxiety, and stress levels in individuals with adverse childhood experiences. This finding informs adults with adverse childhood experiences that managing self-critics may alleviate their mental health problems. Angka kekerasan pada anak tergolong tinggi di Indonesia. Pengalaman buruk di masa kecil dapat membawa dampak buruk pada kesehatan mental individu dewasa. Akan tetapi, asosiasi pengalaman buruk di masa kecil dan masalah kesehatan mental belum banyak diteliti pada konteks Indonesia. Maka dari itu, studi ini menguji pengaruh kritik diri terhadap depresi, kecemasan, dan stres individu dewasa awal yang mengalami pengalaman buruk di masa kecil. Individu dewasa awal yang berusia 18-25 tahun, berdomisili di Indonesia, dan memiliki riwayat pengalaman buruk di masa kecil, dilibatkan sebagai sampel studi (N = 450). Partisipan mengisi kuesioner kritik diri menggunakan alat ukur Levels of Self-Criticism (LOSC) yang mengukur comparative self-criticism dan internalized self-criticism. Depresi, kecemasan, dan stres diukur menggunakan alat ukur Depression, Anxiety, and Stress Scale 42 (DASS-42). Hasil menunjukkan bahwa comparative self-criticism dan internalized self-criticism berkontribusi meningkatkan depresi, kecemasan, dan stres pada individu dewasa awal dengan pengalaman buruk di masa kecil. Hasil ini menjadi informasi penting bagi individu dengan pengalaman buruk di masa kecil bahwa pengelolaan kritik diri bermanfaat untuk mengatasi permasalahan kesehatan mental yang dialami.